Object-Based Viewpoint For Large-Scale Distributed Virtual Environment - Elfizar, Elfizar; Baba, Mohd Sapiyan; Herawan, Tutut (Malaysian Journal of Computer Science, 2015)
Distributed Virtual Environment (DVE) is a shared application consisting many objects, which can be accessed by many users. There have been many methods used to scale the DVE such as dividing simulation workload, dynamic load balancing among servers, and creating alternative architectures. However, they may not accommodate many objects and users. In this paper, we explore all approaches used to scale the DVE and then determine the characteristics of the existing approaches. With those characteristics, we compared existing approaches based on three parameters: the number of simulation per region, implementation, and the number of objects managed by simulator. The results show that all approaches use the same viewpoint, called present viewpoint, in developing the DVE. It views DVE as a world where all objects and activities are managed by a simulator. The results also show that this viewpoint contributes in terms of limitations of the current DVEs performance. In response to these results, we further propose a new viewpoint, called object-based viewpoint, to generate object-based simulators architecture. The experiment results show that our proposed architecture can provide a large scale DVE with better performances than the previous architectures.